Limitation of property interests of juveniles when applying educative measures - А. Panov; I. Serdyukova (Russian Journal of Economics and Law)
RETRACTION:The article published in the scientific Journal “Actual Problems of Economics and Law” (2010. No. 3. Pp. 171–178) under the title “Limitation of property interests of juveniles when applying educative measures” under the authorship of А. А. Panov, I. I. Serdyukova is withdrawn by an editor with the consent of the publisher and the author.Retraction is due to incorrect borrowing from «Uslovnoe osuzhdenie v ugolovnom prave Rossii» dissertatsiya, Alekseev Il'ya Nikolaevich, 2004.http://www.dslib.net/kriminal-pravo/uslovnoe-osuzhdenie-vugolovnom-prave-rossii.html